Polyalcohols from Cassia alata Linn. Seeds - Singh, R.B. (Asian Journal of Chemistry, 2010)
Periodate oxidized carbohydrate of Cassia alata Linn. seeds on reductionproduced polyalcohols as glycerol and erythritol in 0·81 : 2·56 moles.